Cartesian Meditations - Husserl, Edmund. author. aut Link
176 p. 1 illus.
Keywords: The "Cartesian Meditations" translation is based primarily on the printed text, edited by Professor S. Strasser and published in the first volume of Husserliana: Cartesianische Meditationen und Pariser Vorträge, ISBN 90-247-0214-3. Most of Husserl's emendations, as given in the Appendix to that volume, have been treated as if they were part of the text. The others have been translated in footnotes. Secondary consideration has been given to a typescript (cited as "Typescript C") on which Husserl wrote in 1933: "Cartes. Meditationen / Originaltext 1929 / E. Husserl / für Dorion Cairns". Its use of emphasis and quotation marks conforms more closely to Husserl’s practice, as exemplified in works published during his lifetime. In this respect the translation usually follows Typescript C. Moreover, some of the variant readings n this typescript are preferable and have been used as the basis for the translation. Where that is the case, the published text is given or translated in a foornote. The published text and Typescript C have been compared with the French translation by Gabrielle Pfeiffer and Emmanuel Levinas (Paris, Armand Collin, 1931). The use of emphasis and quotation marks in the French translation corresponds more closely to that in Typescript C than to that in the published text. Often, where the wording of the published text and that of Typescript C differ, the French translation indicates that it was based on a text that corresponded more closely to one or the other – usually to Typescript C. In such cases the French translation has been quoted or cited in a foornote.